2014
DOI: 10.1007/s00264-014-2289-y
|View full text |Cite
|
Sign up to set email alerts
|

Influencing factors for the increased stem version compared to the native femur in cementless total hip arthroplasty

Abstract: Since a cementless stem has little version adjustability in the femoral canal, these findings are useful for surgeons in preoperative planning and to achieve proper component placement in THA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 27 publications
5
49
0
Order By: Relevance
“…A further limitation of our study is that all the THAs were performed by a single surgeon and one specific implant geometry. However, other works have previously compared the FNV with the postoperative version and similar discrepancy values were obtained using other methodologies to assess version 22‐28 . For example, Marcovigi et al 22 reported a standard deviation of 9.7 deg for the achieved stem version, with a discrepancy of 1.6 ± 9.8 deg respect to the FNV, while we obtained a version discrepancy of −1.4 ± 8.2 deg.…”
Section: Discussionsupporting
confidence: 85%
“…A further limitation of our study is that all the THAs were performed by a single surgeon and one specific implant geometry. However, other works have previously compared the FNV with the postoperative version and similar discrepancy values were obtained using other methodologies to assess version 22‐28 . For example, Marcovigi et al 22 reported a standard deviation of 9.7 deg for the achieved stem version, with a discrepancy of 1.6 ± 9.8 deg respect to the FNV, while we obtained a version discrepancy of −1.4 ± 8.2 deg.…”
Section: Discussionsupporting
confidence: 85%
“…It has been believed that the difference is related to the stem design. Compared with the double‐wedge stem, the single‐wedge stem is relatively thin, has more freedom in the horizontal plane, and is prone to tilting, which could change the stem anteversion. However, only one measurement method was used in the current study and the study by Taniguchi et al …”
Section: Discussionmentioning
confidence: 99%
“…However, whether measuring femoral anteversion via two‐dimensional CT can predict postoperative stem anteversion remains controversial. Some studies reported that postoperative stem anteversion was predictable, but the results varied widely, with the reported difference between preoperative femoral anteversion and postoperative stem anteversion varying from 2.3° ± 5.9° to 22.7° ± 11.6°, and the correlation coefficient varying from 0.46 to 0.93. Furthermore, some studies found that it was difficult to predict postoperative stem anteversion, especially for the single‐wedge stems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In total hip arthroplasty, version of the femoral component has a narrow window of acceptability . Excessive anteversion or retroversion leads to impingement between the prosthetic neck and acetabular component causing increased wear and instability . As such, femoral neck version must be accurately measured and corrected for long‐term function of the hip joint.…”
mentioning
confidence: 99%